2016
DOI: 10.1098/rsta.2015.0078
|View full text |Cite
|
Sign up to set email alerts
|

Towards rational catalyst design: a general optimization framework

Abstract: Rational catalyst design is one of the most fundamental goals in heterogeneous catalysis. Herein, we briefly review our previous design work, and then introduce a general optimization framework, which converts catalyst design into an optimization problem. Furthermore, an example is given using the gradient ascent method to show how this framework can be used for rational catalyst design. This framework may be applied to other design schemes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…For oxygen‐reduction reaction on Pt(111), they found that sites with same number of first‐nearest neighbors but with increased number of second‐nearest neighbors are more active and subsequently prepared highly active Pt(111) active sites without alloying by three affordable experimental methods. Wang and Hu proposed a general optimization framework for catalyst design: with DFT calculations and micro‐kinetics, the reaction rate can be expressed as a function of the energies of surface species, and the energies of surface species as a function of catalyst structure. Therefore, the reaction rate is finally a function of the catalyst structure.…”
Section: General Understandings and Relationships In The Rational Desmentioning
confidence: 99%
“…For oxygen‐reduction reaction on Pt(111), they found that sites with same number of first‐nearest neighbors but with increased number of second‐nearest neighbors are more active and subsequently prepared highly active Pt(111) active sites without alloying by three affordable experimental methods. Wang and Hu proposed a general optimization framework for catalyst design: with DFT calculations and micro‐kinetics, the reaction rate can be expressed as a function of the energies of surface species, and the energies of surface species as a function of catalyst structure. Therefore, the reaction rate is finally a function of the catalyst structure.…”
Section: General Understandings and Relationships In The Rational Desmentioning
confidence: 99%
“…In Peijun & Wang's paper [13], on the very topic of using DFT for catalyst design, especially those that facilitate the transformation of amides, by hydrogenation, to amides, he showed that single-phase catalysts are of little use.…”
Section: (B) Personal Reflections On the Papers Presented At The Discmentioning
confidence: 99%
“…As suggested in our previous work 14 , rational catalyst design is extremely challenging mainly due to the fact that the relation between surface structure and adsorption energy is still not clear. Recently, Sautet and co-workers 15 reported the excellent example of rational catalyst design based on the generalized coordination number 16,17 .…”
Section: A Rational Catalyst Design Of Co Oxidation Using the Bondingmentioning
confidence: 99%
“…Thus, a more rational approach is highly desirable. As stated in our previous work 14 , the design problem can be treated as searching for the surface structures with desirable adsorption energies. Therefore, a relation to link the hundreds of thousands of alloy surface structures to the corresponding adsorption energies is the key.…”
Section: A Rational Catalyst Design Of Co Oxidation Using the Bondingmentioning
confidence: 99%